TRANSAKSI JUAL BELI TANAH MILIK NEGARA OLEH PENGGARAP TANPA HAK DI KECAMATAN HINAI KABUPATEN LANGKAT - Pratama, Reza Wahyu (Yayasan Daarul Huda Kruengmane, 2021)
The sale and purchase of state-owned land by cultivators without rights in Hinai District, Langkat Regency is contrary to the Government Regulation of the Republic of Indonesia Number 18 of 2001 concerning Management, Land Rights, Flat Units, and Land Registration. In Article 19 letter a it is stated that the community has the right to manage state-owned land for a period of time that has been determined in the legislation but the Malenggang community trades the land without rights, this act causes material losses to one of the parties, namely the land buyer and contrary to Article 1320 of the Civil Code, the condition for the validity of an agreement that the sale and purchase of land without rights carried out by the Malenga community does not meet the requirements for the validity of an agreement.This study aims to analyze the implementation of the sale and purchase of state land by cultivators without rights in Hinai District, Langkat Regency and the legal consequences of buying and selling state land by unauthorized cultivators in Hinai District, Langkat Regency.This research is a qualitative research with an empirical juridical approach. Data obtained through field research (field research). and supported by library data (library research), data analysis was carried out descriptively (descriptive analysis).Based on the results of the study, it is known that the community trades land in the Public Works (PU) environment without rights. So that the sale and purchase carried out causes material losses to the land buyer. The public does not know the legal consequences, namely null and void from the actions taken that the sale and purchase is contrary to the laws and regulations. The research conducted found that the Camat, Village Head and Public Works Service (PU) had not provided advice and counseling to the community in the village of Malengang not to injure buying and selling transactions without rights.It is recommended to the community not to sell and buy land without rights within the Public Works (PU) department and the head of the sub-district head, village head and PU service to provide direct advice and counseling to the community in malengang village so that in the future they do not carry out buying and selling state-owned land. unlawfully.Â